Відбудова шкіл у Волинській області в післявоєнні роки (1944–1953 рр.) - Фазан, Микола Іванович; Fazan, Mykola I. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті аналізується основні напрями державної політики у галузі освіти у післявоєнний період. Дається порівняльний аналіз матеріальних втрат в освіті Волинської області та районів у роки війни. Акцентується увага на відбудові та будівництві шкільних приміщень у 1944–1953 рр.Reconstrection of Volyn Region Schools in Post-War Period. (1944-53 Years.). The specific features of school reconstruction in the post-war period in Volyn region are analized in this article. Special attention is paid to the material base renovation of educational institutions in the region. To determine the extent of necessary remedial work, the comparative analysis of looses on a scale of republics, regions and districs was made. It is demonstrated that the results which were achieved during the post-war years are received owing to joint efforts of public authorities and community. It is maintained that the increasing number of classrooms allowed to change the quality of education, to increase the number of seven-year and secondary schools. Funds invested in the development of school network in 1944 - 1953 became the basis for the Soviet education evolution in subsequent years.
Reconstrection of Volyn Region Schools in Post-War Period. (1944-53 Years.)
Keywords: Волинська область; матеріальні втрати; відбудова та будівництво шкіл; початкова школа; неповна середня освіта; середня школа; післявоєнна п’ятирічка; Volyn region; material losses; school reconstruction and building; elementary school; secondary school; incomplete secondary school; post-war five years